Space management : a practices and approach by Malaysia public universities / Aizam Abdul Aziz ... [et al.] - Abdul Aziz, Aizam; Hashim, Hasnan; Hashim, Ahmad Ezanee; Abdullah Saleh, Alia (2012)
Space is one of major assets of public universities, and on average represents around 29% of the costs of operating an institution. While this incurs a major cost to an institution, the availability of appropriate space is essential to support the teaching, research and community services objectives of institutions. The provision of the right space is becoming even more important as institution are increasingly completing each other for students and funding. The management of space is therefore an essential part of an asset management strategy for any public universities. This study focused on the practice and approaches within four Research University in Klang Valley specific to assess the space management approaches. Approach, in the content of this study is referred to examine and constraint on the various approaches of space management in public universities to improve space use. Therefore, the findings revealed that all four respective public universities implemented different approaches in space management. The differences approach basically influences by the different philosophy and strategy of each organization. Although it found enormous gap in implementation of space management, all the organizations adheres towards optimizing of academic space usage and conducive learning and teaching environment.